Hades, Argentina - Loedel, Daniel (Riverhead Books, 2021)
"In 1976, Tomás Oriilla is a medical student in Buenos Aires, where he's moved in hopes of reuniting with Isabel, a childhood crush. But the reckless passion that has always drawn him is leading Isabel ever deeper into the ranks of young insurgents fighting an increasingly oppressive regime. As its thuggish milicos begin to disappear more and more people like her, she presents Tomás with a way to prove himself. As always, he'll do anything for Isabel. But what exactly is he proving, and at what cost to them both? It will be years before the reckoning arrives, in the form of a call that comes for Tomás, now living as Thomas Shore in New York. An old family friend is dying. But it isn't the chance to say goodbye that pulls him back to Buenos Aires after all these years. It's the memory of her daughter, and what proves to be an undying love. Raising profound questions about the choices we make in the name of love and allegiance, and the hell of unknowable consequences, Hades, Argentina is a gripping, brilliantly narrated literary debut."--Provided by publisher.